Design of triple-bandpass filters using an asymmetric stepped-impedance ring resonator - Wang, Wensong (2018)
An asymmetric stepped-impedance ring resonator (ASIRR) is proposed for the design of a triple-bandpass filter. This resonator is applied to create the former two passbands by utilizing a stepped-impedance circular ring and the third passband by introducing two asymmetric coupling structures. It is found that the S-parameter performance can be improved by adding a pair of shorted and open stubs, and the second passband and the stopbands on both sides of the third passband can be tuned by adjusting the length of open stubs. A prototype filter operating at 1.04, 3.52 and 5.57 GHz is designed, fabricated, and measured with the corresponding fractional bandwidths of 23.1%, 7.4%, and 4.1%. Good agreements between the simulated and measured results are achieved for the ASIRR filter. Also, four transmission zeros are generated.